1992
DOI: 10.1105/tpc.4.2.135
|View full text |Cite
|
Sign up to set email alerts
|

The tomato 66.3-kD polyphenoloxidase gene: molecular identification and developmental expression.

Abstract: A gene coding for a polypeptide abundant in tomato floral meristems was isolated and shown to represent a tomato 66.3-kD polyphenoloxidase. Analysis of cDNA clones and a corresponding intronless genomic clone indicated that the plastid-bound 587-residue-long polypeptide, designated P2, contains two conserved copper-binding domains, similar to those found in funga1 and mammalian tyrosinases. P2 transcripts and polypeptides are accumulated in the arrested floral primordia of the anantha mutant inflorescences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
1
2

Year Published

1993
1993
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 29 publications
6
50
1
2
Order By: Relevance
“…The deduced amino acid sequences of the PPO cDNAs [4,19,35,46], contain N-terminal regions characteristic of plastid transit peptides, and two regions characteristic of tyrosinase CuA and CuB copper binding sites of mammalian, bacterial, and fungal tyrosinases. No evidence exists for genes encoding 40-45 kDa PPOs, nor for PPOs which lack transit peptides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deduced amino acid sequences of the PPO cDNAs [4,19,35,46], contain N-terminal regions characteristic of plastid transit peptides, and two regions characteristic of tyrosinase CuA and CuB copper binding sites of mammalian, bacterial, and fungal tyrosinases. No evidence exists for genes encoding 40-45 kDa PPOs, nor for PPOs which lack transit peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PPO appears to be complex [19,35,46]. Immunogold localization experiments [35] indicate that in the tomato cultivar 'Tiny Tim', PPO is expressed in epidermal cells during early leaflet, floral, and root morphogenesis, and becomes undetectable as the leaflet matures, whereas PPO mRNA in leaflet palisade cells is expressed only in later development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ledenous plants and all encode mature proteins of 56-62 kDa plus an 8-12 kDa transit peptide [2,6,9,11,15,19,21]. PPO has been shown to be encoded by multigene families in broad bean, tomato and potato [6,15,21], but only a single PPO gene was identified in grape berries [91.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic and molecular genetic studies on phenol oxidase are reported on peach (Wong et al ., 1971), mango (Robinson et al ., 1993), potato (Hunt et al ., 1993) and tomato (Shahar et al ., 1992 ; . On the other hand, in the case of barley (Hordeum vulgare L.), varietal variation for the coloring of grains with phenol has been investigated (Takasugi, 1937), but all the varieties tested were stained, more or less, and no inheritance study of the trait has been reported.…”
Section: Introductionmentioning
confidence: 99%